2023
DOI: 10.1126/scitranslmed.adh8005
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-associated fibrosis impairs immune surveillance and response to immune checkpoint blockade in non–small cell lung cancer

Abstract: Non–small cell lung cancer (NSCLC) is a leading cause of cancer-related deaths. Immune checkpoint blockade has improved survival for many patients with NSCLC, but most fail to obtain long-term benefit. Understanding the factors leading to reduced immune surveillance in NSCLC is critical in improving patient outcomes. Here, we show that human NSCLC harbors large amounts of fibrosis that correlates with reduced T cell infiltration. In murine NSCLC models, the induction of fibrosis led to increased lung cancer pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 86 publications
1
3
0
Order By: Relevance
“…Notably, our analysis also indicates that increased SMA expression, reflecting intratumoral fibrosis and cancer-associated fibroblasts, may be associated with worse response to bavituximab plus pembrolizumab 38 40 . This finding is consistent with recent evidence that tumor-associated fibrosis in the lungs impairs immune surveillance and poor responsiveness to checkpoint blockade 41 . These findings may support the potential utility of combining anti-fibrotic therapies with ICIs in fibrotic HCC in future studies.…”
Section: Discussionsupporting
confidence: 93%
“…Notably, our analysis also indicates that increased SMA expression, reflecting intratumoral fibrosis and cancer-associated fibroblasts, may be associated with worse response to bavituximab plus pembrolizumab 38 40 . This finding is consistent with recent evidence that tumor-associated fibrosis in the lungs impairs immune surveillance and poor responsiveness to checkpoint blockade 41 . These findings may support the potential utility of combining anti-fibrotic therapies with ICIs in fibrotic HCC in future studies.…”
Section: Discussionsupporting
confidence: 93%
“…To facilitate the recovery of sufficient numbers of primary cells from tissues and to precisely control the tumor stage, we moved to a transplantable KP line, previously shown to recapitulate most features of autochthonous tumors. 25 , 26 Tissues were harvested after 8 or 28 days, corresponding to early dysplasia, or established adenocarcinoma. Cell-sorted cDC1 were pre-pulsed with an OVA class-I peptide (SIINFEKL) to bypass defective antigen uptake and processing and mixed with functional, OVA-specific CD8 T cells (OT-I) ( Figure 2a ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have suggested that COVID-19 elicits a robust immune response involving both innate and adaptive immunity [11,12]. This heightened immune surveillance might inadvertently target and eliminate precancerous or early-stage lung cancer cells, leading to a reduction in cancer development and progression [13]. However, further studies are required to further clarify these immunological mechanisms involved and their impact on lung cancer biology.…”
Section: Discussionmentioning
confidence: 99%